e-Learning in Practice: Developing the Leadership Learning Environment - Wilson, Casey; Mackness, John (Proceedings of the International Conference on Networked Learning, 2006)
This paper presents the preliminary lessons that have been drawn from an ongoing e-learning project, which aims to develop an e-learning platform and a suite of fully supported e-learning packages for delivery to individual learners who wish to deepen their knowledge, understanding and practice of leadership within the Learning and Skills sector. These lessons are used to suggest some general learning points about the process of developing, delivering and facilitating e-learning in the Learning and Skills sector.